Psychometric properties of the Digital Citizenship Values Scale for high school students - Abbady, Adel Sayed; Teleb, Ahmed Ali; Elsadek, Adel Mohammed; Al-Shehri, Salem Mohammed Ali (International Journal of Innovative Research and Scientific Studies, 2025)
With the increasing integration of digital technologies in education, the need to cultivate responsible digital citizenship among students has become a crucial aspect of modern learning environments. This study aimed to develop and validate a scale to measure digital citizenship values among high school students, focusing on its psychometric properties. The scale was designed based on a comprehensive review of the literature, incorporating three main dimensions: Respect Values, Educational Values, and Protection Values. A sample of 201 high school teachers from Saudi Arabia participated. Data were analyzed using SPSS 26.0 and AMOS 25.0 to assess the scale's validity, reliability, and factor structure. Confirmatory Factor Analysis (CFA) confirmed the three-factor structure, with excellent model fit indices (χ²/df = 2.44, RMSEA = 0.05, CFI = 0.93, TLI = 0.92, GFI = 0.91, AGFI = 0.90). The scale demonstrated high reliability, with Cronbach's alpha values of 0.90 for Respect Values, 0.91 for Educational Values, 0.93 for Protection Values, and 0.94 for the total scale. These findings confirm the scale's validity and reliability, making it a useful tool for measuring digital citizenship values in high school students. The study emphasizes the need to integrate digital citizenship into curricula and lays the groundwork for future research.